Study on the correlation between mountain hazards and soil genesis category in Zhejiang province - WANG Shen-fa; YU Jian-qiang; CHEN He-ping; WANG Shuai; HU Xian-song (浙江大学学报. 农业与生命科学版, 2003)
Based on stratum and tectonic unit and the diversity of mountain hazards, the author selected the typical studying areas. And through the using of the general survey data of mountain hazards and soil and surveying on the spot, the spatial correlation between mountain hazards and soil types was studied. The results show that the mountain hazards mainly occur on 17 soil types. Brown earth, paddy field on brown muddy soil, gravelly yellowish red soil and purple sandstone soil posses the highest density of mountain hazards, And the amount of hazards occur on yellowish red soil, gravelly yellowish red soil and yellow-red soil are larger than that on others.